Analisis Pelanggaran Perjanjian Dalam Perkara Utang Piutang PT. Bank Pembangunan Daerah Nusa Tenggara Timur Cabang Rote Ndao Cq Sender Dewa Lele dengan Debitur (Studi Kasus Putusan No4/Pdt.G.S/2021/PN Rno) - Rizqareka D, Cinta; Afifa, Erina Nur; Tarina, Dwi Desi Yayi (Media Hukum Indonesia (MHI), 2025)
This case originated from a breach of contract (wanprestasi) by the debtor who failed to fulfill the obligation to pay loan installments as agreed in the credit agreement. This study employs a normative juridical method with a case study approach based on a court decision, analyzed qualitatively. The analysis results show that the credit agreement between the two parties was legally valid and met the legal requirements for a valid agreement as stipulated in Article 1320 of the Indonesian Civil Code (KUHPerdata). The panel of judges concluded that the defendant had committed a breach of contract by failing to fulfill her obligations, and therefore ruled that the defendant must repay the debt and cover the court fees. This decision reflects the principles of justice, legal certainty, and legal protection for the creditor.